A qualitative exploration of participant and investigator perspectives from the TRED‐HF trial. (13th August 2021) - Papageorgiou, Vasiliki; Jones, Kathryn; Halliday, Brian P.; Mindham, Richard; Bruton, Jane; Wassall, Rebecca; Cleland, John G.F.; Prasad, Sanjay K.; Ward, Helen
Abstract: Aims: We explored the experiences and motivations of participants and staff who took part in the TRED‐HF trial (Therapy withdrawal in REcovered Dilated cardiomyopathy). Methods and results: We conducted a qualitative study, using semi‐structured interviews, with participants ( n  = 12) and the research team ( n  = 4) from the TRED‐HF trial. Interviews were carried out in 2019 and were audio‐recorded and transcribed. Data were managed using NVivo and analysed using framework analysis. A patient representative provided guidance on the interpretation of findings and presentation of themes to ensure these remained meaningful, and an accurate representation, to those living with dilated cardiomyopathy. Three key themes emerged from the data: (i) perception of health; (ii) experiences and relationships with healthcare services and researchers; and (iii) perception of risk. Study participants held differing perceptions of their health; some did not consider themselves to have a heart condition or disagreed with the medical term 'heart failure'. Relationships between participants, research staff, and clinical management teams influenced participants' experiences and decision making during the trial, including following clinical advice. There were differences in participants' perceptions of risk and their decisions to take heart failure medication after the trial was completed. Although the original TRED‐HF trial did not provide the results many had hoped for, a strong motivator for taking part was the opportunity to withdraw medication in a safely monitored environment which had been previously considered by some participants before. Investigators acknowledged that the insights gained from the study can now be used to support evidence‐based conversations with patients. Conclusions: For people whose dilated cardiomyopathy is in remission, decisions to continue, reduce, or stop their medication are influenced by perceptions of personal health, perceive risk and the important of work, employment, recreation, relationships, and long‐term plans. The unique relationship between patient and cardiologist provides opportunities to promote honest discussion about adherence to medication and personalized long‐term management.